An Economic Analysis of Law on Legal Certainty in the Transition from Contract of Work to Licensing Regime in Indonesian Mining Law - Mohamad Syah Indra Aman; Richard C. Adam (Greenation International Journal of Law and Social Sciences, 2026)
This study examines the transition from the Contract of Work regime to a licensing-based regime in Indonesian mining law through the lens of Economic Analysis of Law, focusing on legal certainty, regulatory efficiency, and transaction costs. The transformation reflects a shift from contractual governance toward an administrative framework that redefines the relationship between the state and investors. This change raises a fundamental tension between investment stability and strengthened state control over natural resources. The objective of this study is to analyze how this institutional transition affects legal certainty and economic efficiency in the mining sector. This research employs a normative juridical method combined with a law and economics approach, operationalized by examining changes in transaction costs, regulatory predictability, and the distribution of authority. The findings indicate that the licensing regime may improve administrative efficiency and reduce coordination costs through centralized control, yet it simultaneously increases regulatory uncertainty and discretionary risks that affect legal predictability. This study argues that the relationship between efficiency and legal certainty is mediated by the quality of regulatory governance. The novelty lies in integrating legal certainty and transaction cost analysis to explain the governance implications of mining law reform in Indonesia.